Morphologic Characteristics of Meniscofemoral Ligaments - ŞEHİRLİ, ÜMİT SÜLEYMAN (ORTADOGU AD PRES & PUBL CO, 2011)
Objective: The aim of this study was to describe the presence, lengths, widths, attachment sites, course of the fibers, histological properties and the sizes of the attachment sites of the meniscofemoral ligaments to the lateral meniscus. Material and Methods: Forty fresh frozen knees obtained from 22 human cadavers were examined. The knee was dissected by posterior approach and the anterior and posterior meniscofemoral and posterior cruciate ligaments were measured after exposing them. The sections of ligaments were stained with the Mason trichrome stain and under light microscope. Results: At least one of the meniscofemoral ligaments was present in 37 (92.5%) cases. Twenty (50%) were anterior meniscofemoral ligaments and 24(60%) were posterior. In seven cases (17.5%) both anterior and posterior meniscofemoral ligaments were present. The oblique fibers of the posterior cruciate ligament were observed in 11 (27.5%) cases. A separating membrane between the meniscofemoral ligaments and the posterior cruciate ligament was observed. The mean lengths of the posterior and anterior meniscofemoral ligaments were 23.82 +/- 1.51 mm and 21.55 +/- 0.97 mm, respectively. The mean widths of the anterior and posterior meniscofemoral ligaments were 3.43 +/- 0.57 mm and 4.09 +/- 0.77 mm, respectively. The mean lengths of the attachment sites of posterior and anterior meniscofemoral ligaments to lateral meniscus were 11.30 +/- 1.85 mm and 6.19 +/- 1.23 mm respectively and the mean widths were 3.39 +/- 0.92 mm and 4.88 +/- 0.96 mm, respectively. Conclusion: Details concerning the dimensions and histological properties of the meniscofemoral ligaments, their relation to the posterior cruciate ligament and lateral meniscus will contribute to a clear understanding of the biomechanics of the knee as well as the radiologic diagnosis and the treatment of knee problems.
Keywords: Knee joint; menisci, tibial; posterior cruciate ligament; POSTERIOR CRUCIATE LIGAMENT; LATERAL MENISCUS; KNEE